2018
DOI: 10.3389/fnagi.2018.00311
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Delirium and Aging: Potential Role of DNA Methylation Change on Cytokine Genes in Glia and Blood Along With Aging

Abstract: Background: Delirium in elderly patients is common and dangerous. Major risk factors include aging and exogenous insults, such as infection or surgery. In animal models, aging enhances pro-inflammatory cytokine release from microglia in response to exogenous insults. The epigenetic mechanism DNA methylation (DNAm) regulates gene expression and changes with age. Older individuals may have methylation changes that influence the increased cytokine upon insult, but the degree to which aging affects DNAm of cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…[74][75][76][77][78] Several world leaders in neonatal neurobiology, actively studying the inflammation-induced sensitization paradigm, are expressing grave concern over the increased risk of neurodegeneration following subsequent insults. 87 Furthermore, alteration of DNA methylation by adverse events can lead to discrepancy between chronological age and methylome age, which is associated to accelerated aging processes and age-related pathologies including neurodegenerative diseases and decreased white matter integrity. DNA methylation is a dynamic process that evolves with age and in pathological conditions.…”
Section: F I G U R E 4 Methylation Levels Of Genes Of Interest Associmentioning
confidence: 99%
“…[74][75][76][77][78] Several world leaders in neonatal neurobiology, actively studying the inflammation-induced sensitization paradigm, are expressing grave concern over the increased risk of neurodegeneration following subsequent insults. 87 Furthermore, alteration of DNA methylation by adverse events can lead to discrepancy between chronological age and methylome age, which is associated to accelerated aging processes and age-related pathologies including neurodegenerative diseases and decreased white matter integrity. DNA methylation is a dynamic process that evolves with age and in pathological conditions.…”
Section: F I G U R E 4 Methylation Levels Of Genes Of Interest Associmentioning
confidence: 99%
“…To fill this gap, we conducted the present study to compare DNAm status in blood from hospitalized patients with and without delirium to identify clinically useful epigenetic biomarkers for delirium from blood samples, which are routinely obtained from patients. We used blood for three reasons: 1) the function of monocytes in the blood is similar to that of microglia in that both release cytokines in response to exogenous stimulus, 2) our comparison of DNAm levels in live brain tissue (resected during neurosurgery) to those in blood from same individual collected at the same time point showed a high level of correlation genome-wide (13), and 3) our previous data showed a similar ageassociated decrease in DNAm in the pro-inflammatory cytokine gene TNF-alpha among glia and blood (12). To accomplish these goals, we conducted the present study investigating DNAm differences in blood between delirium patients and controls without delirium.…”
Section: Introductionmentioning
confidence: 68%
“…This data supports our hypothesis that in pro-inflammatory cytokine genes, DNAm levels decrease along with aging, and expression level increase. In addition, using a unique dataset from our own study comparing DNAm status from neurosurgically resected live human brains followed by fluorescence-activated cell sorting (FACS), we showed that DNAm of the TNF-alpha universally decreases with age among the glial (neuronal negative) component, but no such patterns were found among neurons (neuronal positive component) (12). This data also supports our hypothesis that the DNAm in proinflammatory genes decrease in glia along with aging, making microglia potentially more prone to express those cytokine genes and to have highghtend inflammatory response when exposed to external stimuli such as surgery or infection leading to delirium.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations